Improvement of Participation in Mathematics Learning by Using Cooperative Learning Model Type of Learning Together to Student in Grade VII B of Al-Islam 1 Junior HighSchool of Surakarta Academic Year 2012/2013 (Classroom Action Research) - Permata, Seta Galih, Rita Pramujiyanti Khotimah,S.Si, M.Sc (2013)
This research aims to know the improvement of student's participation in mathematics learning by using cooperative learning model type Learning Together. This research used a qualitative approach by the design of Classroom Action Research (CAR), which is implemented in two cycles. Each cycle have two meetings. Researcher and mathematics teacher grade VII B of Al Islam 1 Junior High School of Surakarta as the subject of the action. The number of students of grade VII B is 25 students as subject that receive the action. Data collection techniques are used: observation, interview, field notes, tests, study document. The data analyzed by descriptive qualitative with three components, there are data reduction, data presentation and data conclusion. Based on the research results it can be concluded that the application cooperative learning model type of Learning Together can improve student's participation in mathematics learning of students grade VII B. It can be seen from several indicators, namely: 1) Actively Involved, increased from 25% to 80%; 2) Asking Questions, increased from 12% to 60%; 3) Proposing Opinion and Advice increased from 8% to 48%; 4) Answering Questions, increased from 16% to 64%; 5) Performance Of The Group On Time, increased from 34% to 100%.